Lacticin 481 Synthetase as a General Serine/Threonine Kinase - You, Young Ok (American Chemical Society, 2009)
[Image: see text] Methods that introduce posttranslational modifications in a general, mild, and non-sequence-specific manner using biologically produced peptides have great utility for investigation of the functions of these modifications. In this study, the substrate promiscuity of a lantibiotic synthetase was exploited for the preparation of phosphopeptides, glycopeptides, and peptides containing analogs of methylated or acetylated lysine residues. Peptides attached to the C-terminus of the leader peptide of the lacticin 481 precursor peptide were phosphorylated on serine residues in a wide variety of sequence contexts by the R399M and T405A mutants of lacticin 481 synthetase (LctM). Serine residues located as many as 30 amino acids C-terminal to the leader peptide were phosphorylated. Wild-type LctM was shown to dehydrate these peptides to generate dehydroalanine-containing products that can be conveniently modified with external nucleophiles including thiosaccharides, 2-(dimethylamino)ethanethiol, and N-acetyl cysteamine, resulting in mimics of O-linked glycopeptides and acetylated and methylated lysines.